High-strength carbon dioxide corrosion resistant oil casing and manufacturing method thereof

By rationally designing chemical element components and process technology, high-strength and excellent corrosion resistance of CO2 are prepared, which solves the problem of high cost and insufficient strength of existing materials, and achieves efficient and economical improvement of material performance.

CN119464921AActive Publication Date: 2025-02-18BAOSHAN IRON & STEEL CO LTD

Patent Information

Application Number
CN202310997786.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18
Estimated Expiration
2043-08-09

AI Technical Summary

Technical Problem

The existing oil casing materials that resist CO2 corrosion are costly and have insufficient strength, making it difficult to meet the needs of high strength and excellent corrosion resistance at the same time.

Method used

By rationally designing chemical element components, including low-carbon components, appropriate amounts of Cr elements and Ni, Mo, V, Ce, and La elements, using quenching and tempering processes, oils with high yield strength and excellent corrosion resistance against CO2 are prepared by using quenching and tempering. casing.

Benefits of technology

The high yield strength (up to 140ksi) of the oil casing and excellent corrosion resistance of CO2 are achieved, which significantly improves the service life of the casing and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464921A_ABST
    Figure CN119464921A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength carbon dioxide corrosion resistant oil casing pipe, which contains Fe and inevitable impurities, and further contains the following chemical elements: 0.10 to 0.20 percent of C, 0.10 to 0.80 percent of Si, 0.10 to 1.50 percent of Mn, 3 to 5 percent of Cr, 0.10 to 0.70 percent of Mo, 0.01 to 0.10 percent of Al, 0.10 to 0.20 percent of V, 0.1 to 1.0 percent of Ni, 0.002 to 0.01 percent of Ce and 0.002 to 0.01 percent of La. Correspondingly, the invention further discloses a manufacturing method of the high-strength carbon dioxide corrosion resistant oil casing. Through reasonable chemical element composition design, the oil casing with ultrahigh strength and excellent carbon dioxide corrosion resistance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a steel material and a manufacturing method thereof, in particular to an oil casing and a manufacturing method thereof. Background Art

[0002] In the process of oil and gas development, corrosion problems often lead to great economic losses or even catastrophic consequences. Many current oil fields have serious CO2 corrosion problems.

[0003] Although a lot of research has been done at home and abroad to develop 13Cr steel resistant to CO2 corrosion and high corrosion-resistant Ni-based alloys, the above materials contain a large amount of precious metal elements such as Cr, Ni, and Mo, which leads to a significant increase in the cost of steel pipes.

[0004] In the prior art, most alloy steels used for resistance to CO2 corrosion (or resistance to CO2+H2S+Cl- combined corrosion) are medium alloy or high alloy component systems such as 13Cr, and the low alloy 3Cr series corrosion-resistant oil casing has low strength and cannot reach above 110ksi steel grade.

[0005] For example, the Chinese patent document with publication number CN101899621A, publication date December 1, 2010, and titled “A 3Cr seamless steel pipe and its manufacturing method” has a chemical composition of C: 0.1-0.2%, Si: 0.1-0.5%, Mn: 0.3-0.8%, Cr: 2-4%, Mo: 0.3-0.6%, Ti: 0.0024-0.024%, Al: 0.01-0.04%, P≤0.03%, S≤0.03%, and the remainder is Fe and unavoidable impurities. The tempering heat treatment process is adopted to achieve a yield strength ≥552MPa, i.e. 80ksi.

[0006] For another example, the Chinese patent document with publication number CN103602903A, publication date February 26, 2014, and titled “A high-strength carbon dioxide corrosion-resistant oil well pipe and its manufacturing method” has a chemical composition of C: 0.30-0.42%, Si: 0.10-1.0%, Mn: 0.80-1.5%, Cr: 0.5-1.5%, V: 0.21-0.4%, Al: 0.01-0.10%, N: 0.031-0.05%, P≤0.015%, S≤0.005%, the remainder is Fe and unavoidable impurities, the V / N ratio is controlled at 6-11, and the normalizing process is adopted, and the mechanical properties reach above 95ksi steel grade. Summary of the invention

[0007] One of the purposes of the present invention is to provide a high-strength oil casing and tubing resistant to carbon dioxide corrosion, which can obtain an oil casing and tubing having both ultra-high strength and excellent carbon dioxide corrosion resistance through reasonable chemical element composition design.

[0008] In order to achieve the above object, the present invention provides a high-strength carbon dioxide corrosion-resistant oil casing, which contains Fe and inevitable impurities, and also contains the following chemical elements in the following mass percentages:

[0009] C: 0.10~0.20%, Si: 0.10~0.80%, Mn: 0.10~1.50%, Cr: 3~5%, Mo: 0.10~0.70%, Al: 0.01~0.10%, V: 0.10~0.20%, Ni: 0.1~1.0%, Ce: 0.002~0.01%, La: 0.002~0.01%.

[0010] Accordingly, the present invention also provides a high-strength carbon dioxide corrosion-resistant oil casing, the mass percentage of each element of which is:

[0011] C: 0.10~0.20%, Si: 0.10~0.80%, Mn: 0.10~1.50%, Cr: 3~5%, Mo: 0.10~0.70%, Al: 0.01~0.10%, V: 0.10~0.20%, Ni: 0.1~1.0%, Ce: 0.002~0.01%, La: 0.002~0.01%; the balance is Fe and other inevitable impurities.

[0012] Generally speaking, in order to improve the material's resistance to CO2 corrosion, a certain amount of Cr is usually added to form a dense corrosion film to protect the base material. However, Cr and C are easy to combine to form carbides. 23C6 and C7C3 cannot form a Cr(OH)3 corrosion film with anion selectivity, so the present invention adopts a low-carbon component design to reduce the carbide content of Cr to promote the formation of corrosion film Cr enrichment, improve the stability of the corrosion film and thus improve the corrosion resistance. At the same time, Ce and La elements are added. On the one hand, they have a strong affinity with elements such as O and S, and can be deeply deoxidized to form rare earth compounds for easy smelting and impurity removal, thereby reducing the content of coarse inclusions and preventing pitting pits from forming at the location of larger inclusions. On the other hand, rare earths reduce the crystallization supercooling, resulting in the refinement of the solidification process. Rare earth modification forms uniformly dispersed fine rare earth inclusion particles, which can be used as the second phase nucleation core, and can also produce a grain boundary pinning effect, which is conducive to grain refinement and promotes the improvement of comprehensive performance. In addition, the V, Ni, Nb multi-element microalloying component design enables the present invention to achieve a high yield strength of 140ksi, while improving the corrosion resistance, the anti-collapse performance of the casing is improved, thereby significantly improving the service life of the casing.

[0013] Specifically, in the high-strength carbon dioxide corrosion-resistant oil casing of the present invention, the design principles of the chemical elements are as follows:

[0014] C: In the high-strength carbon dioxide corrosion-resistant oil casing described in the present invention, C is the main solid solution strengthening element and can improve the strength of steel. However, too high a content will worsen segregation, reduce toughness, and form carbides that will damage corrosion resistance. Therefore, the present invention controls the C content to 0.10-0.20%.

[0015] Si: In the high-strength carbon dioxide corrosion-resistant oil casing described in the present invention, Si is a deoxidizer and has a strong solid solution strengthening effect on ferrite, improving hardenability, tempering resistance, and yield strength. However, too high a content will deteriorate the toughness and processing performance of the steel. Therefore, the present invention controls the Si content to 0.10-0.80%.

[0016] Mn: In the high-strength carbon dioxide corrosion-resistant oil casing described in the present invention, Mn is one of the important alloying elements, which strongly improves the hardenability of steel and promotes the formation of martensite to ensure strength. However, too high a content has an unfavorable tendency to promote grain coarsening and structural segregation. Therefore, the present invention controls the Mn content to 0.10-1.50%.

[0017] Cr: In the high-strength carbon dioxide corrosion-resistant oil casing of the present invention, Cr is the main alloying element for improving corrosion resistance and can increase the hardenability of steel, so the Cr content is controlled to be 3-5% in the present invention.

[0018] Mo: In the high-strength carbon dioxide corrosion-resistant oil casing described in the present invention, Mo has a strong ability to inhibit the transformation of austenite to pearlite, can inhibit temper brittleness, form dispersed special carbides at a higher tempering temperature, and improve strength. Based on this, the present invention controls the Mo content to 0.10-0.70%.

[0019] Al: In the high-strength carbon dioxide corrosion-resistant oil casing of the present invention, Al is mainly used for deoxidation and grain refinement, and has a great solid solution strengthening effect. Based on this, the present invention controls the Al content to be 0.01-0.10%.

[0020] V: In the high-strength carbon dioxide corrosion-resistant oil casing described in the present invention, V is a strong carbide and nitride forming element, which improves the tempering resistance of steel and has a strong secondary hardening effect. It is solid-dissolved in ferrite and has a very strong solid-solution strengthening effect. However, if the V content is too high, coarse V (C, N) is easily formed, which damages the toughness. Therefore, the V content is controlled to 0.10-0.20% in the present invention.

[0021] Ni: Ni has a certain solid solution strengthening effect and can improve the corrosion resistance. In the high-strength carbon dioxide corrosion-resistant oil casing described in the present invention, Ni is used in combination with Cr and Mo to improve the thermal strength and corrosion resistance of steel. Based on this, the present invention controls the Ni content to 0.1-1.0%.

[0022] Ce, La: In the high-strength carbon dioxide corrosion-resistant oil casing described in the present invention, trace amounts of Ce and La are added to refine grains and improve toughness, but excessive content thereof is prone to form coarse oxides or sulfur oxides. Therefore, the present invention controls the contents of Ce and La to 0.002-0.01%.

[0023] Furthermore, in the high-strength carbon dioxide corrosion-resistant oil casing of the present invention, the mass percentage of each chemical element may further satisfy at least one of the following items:

[0024] Si: 0.1-0.4%;

[0025] Mn: 0.2-1.0%;

[0026] Mo: 0.4-0.6%;

[0027] Al: 0.01~0.04%;

[0028] Ni: 0.1-0.5%;

[0029] Ce: 0.002~0.008%;

[0030] La: 0.002~0.005%.

[0031] Furthermore, the high-strength carbon dioxide corrosion-resistant oil casing of the present invention also contains 0<Nb≤0.15wt%.

[0032] Nb has a strong solid solution strengthening effect and can refine grains. A trace amount of Nb can improve the strength of steel without affecting plasticity and toughness. Based on this, in some embodiments of the present invention, its content is controlled to be 0<Nb≤0.15wt%.

[0033] Furthermore, among the inevitable impurities in the high-strength carbon dioxide corrosion-resistant oil casing of the present invention: P≤0.015%, S≤0.008%, and N≤0.008%.

[0034] Furthermore, P is controlled to be ≤ 0.012%, S ≤ 0.005%, and N ≤ 0.006%.

[0035] In the above technical solution of the present invention, P, S and N are all harmful impurity elements, among which P and S are severely segregated in steel, which is unfavorable to plasticity and toughness. N has no significant strengthening effect, forms nitrides that damage the strengthening effect of micro-alloying elements, and easily causes aging hardening of low-carbon steel, reducing plasticity and toughness. Therefore, in order to obtain steel with better performance and better quality, the content of P, S and N should be reduced as much as possible under the condition that technology allows.

[0036] Furthermore, in the high-strength carbon dioxide corrosion-resistant oil casing of the present invention, its microstructure matrix is ​​tempered troostite.

[0037] Furthermore, in the high-strength carbon dioxide corrosion-resistant oil casing of the present invention, the grain size is above level 10.

[0038] Furthermore, in the high-strength carbon dioxide corrosion-resistant oil casing of the present invention, the percentage of large-sized inclusions with an average diameter greater than 5 μm in the total inclusions is less than 6%.

[0039] Furthermore, in the high-strength carbon dioxide corrosion-resistant oil casing of the present invention, the Cr content in the corrosion product film is higher than 13wt%.

[0040] Furthermore, the high-strength carbon dioxide corrosion-resistant oil casing of the present invention has the following properties: yield strength of 965-1173 MPa, tensile strength ≥1034 MPa, and 0°C transverse Charpy impact energy ≥80 J.

[0041] Furthermore, the high-strength carbon dioxide corrosion-resistant oil casing of the present invention has a uniform corrosion rate of ≤2.5 mm / a under the corrosive environment conditions of a temperature of 60° C., a CO 2 partial pressure of 1 MPa, and a NaCl concentration of 20 g / L.

[0042] Correspondingly, another object of the present invention is to provide a method for manufacturing the above-mentioned high-strength carbon dioxide corrosion-resistant oil casing, which has a simple process and low production cost.

[0043] In order to achieve the above object, the present invention proposes a method for manufacturing the above-mentioned high-strength carbon dioxide corrosion-resistant oil casing, which comprises the following steps:

[0044] (1) smelting and continuous casting to obtain tube blanks;

[0045] (2) Heating, perforating, rolling and sizing;

[0046] (3) Quenching: The quenching temperature is 880-920°C, and the temperature is kept for 30-60 minutes before water quenching;

[0047] (4) Tempering: The tempering temperature is 550-650℃ and the holding time is 45-75min.

[0048] Furthermore, in step (1) of the manufacturing method of the present invention, the superheat of the molten steel is controlled to be ≤30°C during the casting process, and the continuous casting speed is controlled to be below 2.0 m / min.

[0049] Furthermore, in step (2) of the manufacturing method of the present invention, the mixture is heated to an average temperature of 1200 to 1250° C. and kept warm for 100 to 300 minutes.

[0050] Furthermore, in step (2) of the manufacturing method of the present invention, the perforation temperature is controlled to be 1150-1250°C.

[0051] Furthermore, in step (2) of the manufacturing method of the present invention, the final rolling temperature is controlled to be 900-1000°C.

[0052] Furthermore, in step (2) of the manufacturing method of the present invention, the sizing temperature is controlled to be 850-950°C.

[0053] The high-strength carbon dioxide corrosion-resistant oil casing and its manufacturing method of the present invention have the following advantages and beneficial effects:

[0054] The high-strength carbon dioxide corrosion-resistant oil casing of the present invention is designed with low carbon components, and is added with appropriate Cr elements, as well as Ni, Mo, V, Ce, and La elements, so that the produced oil casing has high strength and excellent corrosion resistance.

[0055] In some embodiments, the high-strength carbon dioxide corrosion-resistant oil casing of the present invention has a yield strength of 965-1173 MPa, reaching 140 ksi, a tensile strength ≥1034 MPa, and a 0°C transverse Charpy impact energy ≥80 J, and has excellent mechanical properties.

[0056] In some embodiments, the high-strength carbon dioxide corrosion-resistant oil casing described in the present invention has a uniform corrosion rate of ≤2.5mm / a under the corrosive environment conditions of temperature 60°C, CO2 partial pressure 1MPa, and NaCl concentration 20g / L, and thus has excellent carbon dioxide corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a microstructure photograph of the oil casing of Example 1 of the present invention under an optical microscope.

[0058] Figure 2 This is a microstructure photograph of the oil casing of Example 1 of the present invention under a scanning electron microscope.

[0059] Figure 3 This is a microstructure photograph of the oil casing of Comparative Example 1 under a scanning electron microscope. DETAILED DESCRIPTION

[0060] The high-strength carbon dioxide corrosion-resistant oil casing and its manufacturing method described in the present invention will be further explained and illustrated in combination with specific embodiments and drawings of the specification. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.

[0061] Examples 1-18 and Comparative Examples 1-5

[0062] The high-strength carbon dioxide corrosion-resistant oil casings of Examples 1-18 are all prepared by the following steps:

[0063] (1) Smelting: The smelting is carried out by primary refining, refining outside the furnace and vacuum degassing. The tapping temperature can be 1600-1700℃.

[0064] (2) Continuous casting: The round billet is produced by continuous casting process, the superheat of molten steel is controlled to be ≤30℃, and the continuous casting speed is controlled below 2.0m / min.

[0065] (3) The round billet is heated in a ring heating furnace to an even temperature of 1200-1250°C, kept warm for 100-300 min, and then pierced at a piercing temperature of 1150-1250°C.

[0066] (4) Rolling: Continuous rolling is carried out after piercing, and the final rolling temperature is controlled at 900-1000℃.

[0067] (5) Sizing: After a short heating in the heating furnace, sizing is carried out and the sizing temperature is controlled at 850-950°C.

[0068] (6) Quenching: Heat to 880-920℃ and keep at this temperature for 30-60min, then quench in water.

[0069] (7) Tempering: The tempering temperature is 550-650℃, and the holding time is 45-75min.

[0070] It should be noted that the contents of chemical elements in Comparative Examples 1-5 are not in accordance with the design of the present invention.

[0071] Table 1 lists the mass percentages of the chemical elements in the high-strength carbon dioxide corrosion-resistant oil casing of Examples 1-18 and the comparative oil casing of Comparative Examples 1-5.

[0072] Table 1. (wt%, the balance is Fe and other inevitable impurities except P, S, N)

[0073]

[0074]

[0075] Table 2 lists the specific process parameters of the high-strength carbon dioxide corrosion-resistant oil casing of Examples 1-18 and the comparative oil casing of Comparative Examples 1-5 in the above process steps.

[0076] Table 2.

[0077]

[0078]

[0079]

[0080] The high-strength carbon dioxide corrosion-resistant oil casing of Examples 1-18 and the comparative pipes of Comparative Examples 1-5 were sampled respectively, and statistics of large-sized inclusion particles with an average diameter of >5 μm and grain size measurement were performed. The obtained test results are listed in Table 3.

[0081] Table 3.

[0082]

[0083] It can be seen from Table 3 that the grain sizes of the embodiments of the present invention are all above level 10, and the percentage of large-sized inclusions with an average diameter greater than 5 μm accounts for less than 6% of the total inclusions. The grain sizes of comparative examples 4 and 5 are lower than level 10, and the percentage of large-sized inclusions is also much higher than that of the embodiments of the present invention.

[0084] also, Figure 1 The microstructure photo of the oil casing of Example 1 of the present invention under an optical microscope is shown. Figure 1 It can be seen that the microstructure of Example 1 at room temperature is a tempered troostite structure.

[0085] Figure 2The microstructure photo of the oil casing of Example 1 of the present invention under a scanning electron microscope is shown. Figure 2 It can be seen that the microstructure of Example 1 is distributed with a small amount of fine dispersed carbides.

[0086] Figure 3 The microstructure photo of the oil casing of Comparative Example 1 under a scanning electron microscope is shown. Figure 3 It can be seen that the microstructure of Comparative Example 1 contains a lot of coarse carbides, which is not conducive to corrosion resistance.

[0087] In addition, samples of the high-strength carbon dioxide corrosion-resistant oil casing of Examples 1-18 and the comparative pipes of Comparative Examples 1-5 were taken for mechanical property tests and corrosion resistance tests, and the test results are listed in Table 4. The relevant test process is as follows:

[0088] Refer to the standard GB / T 228.1-2021 "Tensile tests on metallic materials - Part 1: Room temperature tensile test method" for room temperature tensile performance tests.

[0089] V-shaped impact specimens were processed and the 0°C impact performance test was carried out with reference to the standard GB / T 229-2020 "Charpy Pendulum Impact Test Method for Metallic Materials".

[0090] With reference to the standard JB / T 7901-1999 “Method for laboratory uniform corrosion full immersion test of metal materials”, the corrosion pieces were sampled and processed, and the test was carried out in a high-temperature and high-pressure autoclave under the corrosion environment conditions of temperature 60°C, CO2 partial pressure 1MPa, NaCl concentration 20g / L, rotation speed 1m / s, and test period 168h. The uniform corrosion rate was measured and the cross-section of the corrosion piece was analyzed using SEM+EDS.

[0091] Table 4 lists the test results of the high-strength carbon dioxide corrosion-resistant oil casing of Examples 1-18 and the comparative oil casing of Comparative Examples 1-5.

[0092] Table 4.

[0093]

[0094]

[0095] It can be seen from Table 4 that the yield strength of the high-strength carbon dioxide corrosion-resistant oil casing of Examples 1-18 of the present invention is higher than 965 MPa, the tensile strength is higher than 1034 MPa, and the 0°C transverse Charpy impact energy is greater than 80 J. At the same time, under the test corrosion environment, the Cr content in the corrosion product film of each embodiment of the present invention is higher than 13wt%, and the uniform corrosion rate is lower than 2.5mm / a.

[0096] However, since the chemical element contents of comparative examples 1 to 5 do not meet the design requirements of the present invention, their corrosion performance is inferior to that of the present invention, and their mechanical properties are also poor.

[0097] It can be seen that by adopting the technical solution described in the present invention, an oil casing with both ultra-high strength and carbon dioxide corrosion resistance can be obtained.

[0098] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.

[0099] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.

Claims

1. A high-strength carbon dioxide corrosion-resistant oil casing, containing Fe and inevitable impurities, characterized in that: It also contains the following chemical elements in the following mass percentages: C: 0.10~0.20%, Si: 0.10~0.80%, Mn: 0.10~1.50%, Cr: 3~5%, Mo: 0.10~0.70%, Al: 0.01~0.10%, V: 0.10~0.20%, Ni: 0.1~1.0%, Ce: 0.002~0.01%, La: 0.002~0.01%.

2. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1, characterized in that: The mass percentage of each element is: C: 0.10~0.20%, Si: 0.10~0.80%, Mn: 0.10~1.50%, Cr: 3~5%, Mo: 0.10~0.70%, Al: 0.01~0.10%, V: 0.10~0.20%, Ni: 0.1~1.0%, Ce: 0.002~0.01%, La: 0.002~0.01%; the balance is Fe and other inevitable impurities.

3. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1 or 2, characterized in that: The mass percentage of each chemical element further satisfies at least one of the following items: Si: 0.1-0.4%; Mn: 0.2-1.0%; Mo: 0.4-0.6%; Al:0.01~0.04%; Ni: 0.1-0.5%; Ce: 0.002~0.008%; La: 0.002~0.005%.

4. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1 or 2, characterized in that: It also contains 0<Nb≤0.15wt%.

5. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1 or 2, characterized in that: Among the unavoidable impurities: P ≤ 0.015%, S ≤ 0.008%, N ≤ 0.008%.

6. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1 or 2, characterized in that: Its microstructure matrix is ​​tempered troostite.

7. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1 or 2, characterized in that: Its grain size is above level 10.

8. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1 or 2, characterized in that: The percentage of large inclusions with an average diameter greater than 5 μm is less than 6% of all inclusions.

9. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 6, characterized in that: The Cr content in its corrosion product film is higher than 13wt%.

10. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1 or 2, characterized in that: Its performance meets the following requirements: yield strength is 965~1173MPa, tensile strength is ≥1034MPa, and 0℃ transverse Charpy impact energy is ≥80J.

11. The high-strength carbon dioxide corrosion-resistant oil casing according to claim 1 or 2, characterized in that: Its uniform corrosion rate under the corrosive environment conditions of temperature 60℃, CO2 partial pressure 1MPa, and NaCl concentration 20g / L is ≤2.5mm / a.

12. The method for manufacturing a high-strength carbon dioxide corrosion-resistant oil casing according to any one of claims 1 to 11, characterized in that: It includes the steps of: (1) smelting and continuous casting to obtain tube blanks; (2) Heating, perforating, rolling and sizing; (3) Quenching: The quenching temperature is 880-920°C, and the temperature is kept for 30-60 minutes before water quenching; (4) Tempering: The tempering temperature is 550-650℃ and the holding time is 45-75min.

13. The manufacturing method according to claim 12, characterized in that: In step (1), during the casting process, the superheat of the molten steel is controlled to be ≤30°C, and the continuous casting speed is controlled to be below 2.0 m / min.

14. The manufacturing method according to claim 12, characterized in that: In step (2), the mixture is heated to an average temperature of 1200 to 1250° C. and kept at this temperature for 100 to 300 minutes.

15. The manufacturing method according to claim 12, characterized in that: In step (2), the perforation temperature is controlled to be 1150-1250°C.

16. The manufacturing method according to claim 12, characterized in that: In step (2), the final rolling temperature is controlled to be 900-1000°C.

17. The manufacturing method according to claim 12, characterized in that: In step (2), the sizing temperature is controlled to be 850-950°C.

Citation Information

Patent Citations

  • 3Cr seamless steel pipe and production method thereof

    CN101899621A

  • High-strength carbon dioxide corrosion-resisting oil well pipe and manufacturing method thereof

    CN103602903A

  • Rear-earth-containing CO2-resistant economical sleeve material and preparation method thereof

    CN103131952A

  • Anti-CO2 corrosion oil well pipe below 150 ksi produced by CPE unit and production method thereof

    CN104451394A

  • Cr-containing steel tube excellent in carbon dioxide corrosion resistance and sour resistance

    JP1999269608A

Cited By

  • Corrosion-resistant oil casing and preparation method thereof

    CN121629268A